An Integrated Framework for Learning Fuzzy Cognitive Map using RCGA and NHL Algorithm - Zhu, Yanchun; Zhang, Wei (2008 4th International Conference on Wireless Communications, Networking and Mobile Computing, 2008)
The methodology of developing fuzzy cognitive map (FCM) still exhibited weaknesses. This paper investigated a hybrid framework for learning FCM, which was combined of the real-coded genetic (RCGA) algorithm and nonlinear Hebbian learning (NHL) algorithm. This approach combined the synergistic theories of neural networks and fuzzy logic. The hybrid algorithm is introduced, presented and applied successfully in real-world problems of partner selection.